Monitoring of shallow landslide in Tun Sardon 3.9 km Penang Island, Malaysia - Mohammad Muqtada Ali Khan; Habibah Lateh (Academic Journals, 2011)
The objective of this paper is to monitor the slope movement before a landslide occurrence. Inclinometer, piezometer and rain gauge were installed to monitor the slope. In the study area, water level of all piezometers is showing cyclic trend correlated with rainfall intensity. Observation made on July 30th 2010 and November 4th 2010 show soil movement in positive direction (towards slope). A relation between soil movement and high intensity of rainfall during this period was inferred which can be consider as a potential threat for mankind.